2003
DOI: 10.1242/jeb.00523
|View full text |Cite
|
Sign up to set email alerts
|

Flexural stiffness in insect wings I. Scaling and the influence of wing venation

Abstract: SUMMARYDuring flight, many insect wings undergo dramatic deformations that are controlled largely by the architecture of the wing. The pattern of supporting veins in wings varies widely among insect orders and families, but the functional significance of phylogenetic trends in wing venation remains unknown, and measurements of the mechanical properties of wings are rare. In this study, we address the relationship between venation pattern and wing flexibility by measuring the flexural stiffness of wings (in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
441
2
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 482 publications
(458 citation statements)
references
References 31 publications
13
441
2
2
Order By: Relevance
“…Previous studies [13,15,29,33,34] suggested that the inertial loads are higher than the aerodynamic loads, from 2 [31] up to 10 times [34]. If such a load ratio also holds for dragonfly wings is unknown.…”
Section: Dragonfly Forewing Loadingmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies [13,15,29,33,34] suggested that the inertial loads are higher than the aerodynamic loads, from 2 [31] up to 10 times [34]. If such a load ratio also holds for dragonfly wings is unknown.…”
Section: Dragonfly Forewing Loadingmentioning
confidence: 99%
“…To check if the number of elements in our FEM model was appropriate for numerical convergence we performed a literature survey. Combes and Daniel [13][14][15] found an asymptotic solution for their FEM model of a Manduca sexta wing for 865 elements and up (FEM solver MSC Marc/Mentat 2001). Considering the similarity in wing dimensions and number of elements and the quality of the solution we obtained, we are confident we performed an accurate FEM analysis.…”
Section: The Finite Element Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…For our purpose, it is sufficient to address only the chordwise flexibility and represent the flexible wing as a homogeneous elastic flat plate [24]. While three-dimensional effects, such as spanwise flow that seem to stabilize the LEVs [25] or LEV-tip-vortex interaction [26] are notable in general, the chordwise flexibility is essential and warrants an independent study [18].…”
Section: Introductionmentioning
confidence: 99%